(untitled) (Reflection and Critique Law Magazine, 2020)
Provision No. 260/2013 of the Corregedoria Geral da Justiça of Minas Gerais instituted Estremação, with the purpose of regularizing parcels of rural properties registered in condominium, but in a consolidated and located situation and with a minimum tenure of five years by the owner. In the "pro diviso" condominium, the fraction of each owner is perfectly determined on the spot, wired and used exclusively by the owner. In order to regularize a rural property, one of the procedures to be followed is the location of the parcel and, consequently, the consent of the claimants. The instrumentalization of the act is carried out by means of a declaratory public deed. Only the property with an area equal to or greater than the minimum fraction of installments may be the object of a declaratory deed of location, the size of which the remaining property must also obey. The description of the property must be in accordance with the Public Records Law and natural limits and exchanges of confrontants must be respected. When it comes to locating a parcel with rectification of the area, a map, memorial and ART will be required. If there is no rectification of the area, the need to present clarifying documents will be at the discretion of the Notary. In practice, everyone asks as shown in this article. It appears that this instrument has a social purpose with regard to the inclusion of rural landowners in the state system of agricultural financing, as currently there has been a refusal to accept rural properties registered in condominium as collateral, although in fact these properties have foreign currency. certain and determined. Also, it is clear that Estremação came to assist in the georeferencing of rural properties with the National Institute of Colonization and Agrarian Reform (INCRA), because if the registration is in a condominium, the fractions of the other tenants must be measured. This article aims to disseminate and assist the authors of condominium extinction works, briefly describing the procedures for using this important instrument.